2016
DOI: 10.1097/dcr.0000000000000700
|View full text |Cite
|
Sign up to set email alerts
|

Fistula-Associated Anorectal Cancer in the Setting of Crohn’s Disease

Abstract: Routine biopsies of long-standing fistula tracts in patients with Crohn's disease should be strongly considered and may yield an earlier diagnosis of cancer in the fistula tracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 12 publications
2
27
0
1
Order By: Relevance
“…The characteristics of 52 studies reporting data from 208 patients with ARC are shown in Table 2 11,15,19,23,25,28,30,34,36–80 . Although many reports did not describe the details of each characteristic, the median survival prognosis was 2.1 ± 2.3 years in 74 patients, and advanced cancer greater than stage T3 occurred in 46/74 (62.1%) patients.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of 52 studies reporting data from 208 patients with ARC are shown in Table 2 11,15,19,23,25,28,30,34,36–80 . Although many reports did not describe the details of each characteristic, the median survival prognosis was 2.1 ± 2.3 years in 74 patients, and advanced cancer greater than stage T3 occurred in 46/74 (62.1%) patients.…”
Section: Resultsmentioning
confidence: 99%
“…Fistula-associated adenocarcinomas can develop in patients with chronic perianal CD 207208. The incidence is very rare, however, and was reported at 0.2/1,000 patient-years in CD patient in a meta-analysis of 20 clinical studies published from 1965 to 2008 209.…”
Section: Cancer Surveillancementioning
confidence: 99%
“…The success rate of Nigro protocol was 75% in their series, similar to anal SCC without Crohn's disease [12]. The authors concluded that there might be a benefit to performing resection in these patients in order to avoid the harmful effect of radiation, which could be added later if necessary [12]. Our patient was managed in a similar manner.…”
Section: Discussionmentioning
confidence: 56%
“…Shwaartz et al reported their experience of treating nine patients with squamous cell carcinoma of perianal Crohn's fistula [12]. Two-thirds of the patients received neoadjuvant chemoradiation and did not require abdominoperineal resection (APR); however, one-third of the patients had recurrent/persistent disease ultimately requiring APR [12]. The success rate of Nigro protocol was 75% in their series, similar to anal SCC without Crohn's disease [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation